Role of FNAC in the diagnosis of cervical lymphadenopathy - Janagam, Chandralekha; Atla, Bhagyalakshmi (International Journal of Research in Medical Sciences, 2017)
Background: Cervical lymphadenopathy is one of the commonest presentations in inflammatory and neoplastic disorders. Fine Needle Aspiration Cytology (FNAC) is simple, quick, inexpensive and minimally invasive OPD technique used for establishing the etiology of cervical lymphadenopathy. In this study we describe cytomorphological patterns of cervical lymph nodes and its utility in establishing diagnosis. Objectives of present study were to assess the distribution of various cytomorphological patterns of cervical lymphadenopathy and to assess the age specific distribution of various cytomorphological patterns of cervical lymphadenopathy. Methods: This study was carried out in the Department of Pathology, Andhra Medical College on 200 cases of cervical lymphadenopathy over a period of three months from August - October 2017. FNAC diagnosis was correlated with relevant clinical findings and investigations. Results: Total 200 cases were studied. Of these, 170 (85%) were inflammatory and 30 (15%) were neoplastic. Reactive non-specific lymphadenitis was the most common disease found in 95 (47.5%) patients followed by tuberculous lymphadenitis in 60 patients (30%) and granulomatous lymphadenitis in 15 patients (7.5%). Among neoplastic lesions, metastatic tumours were reported in 26 patients (13%) and Lymphoproliferative disorder/Lymphoma was reported in 4 patients (2%). Highest incidence of cervical lymphadenopathy was found in patients of 10-39 years age group, among which most of the cases were non-specific lymphadenitis followed by tuberculous lymphadenitis. Amongst the neoplastic lesions, most of the cases were in the age group of 40-79 years. Conclusions: FNAC is simple, safe, reliable procedure for diagnosis of cervical lymphadenopathy.